PATIENT AND PUBLIC INVOLVEMENT IN EARLY AWARENESS AND ALERT ACTIVITIES: AN EXAMPLE FROM THE UNITED KINGDOM. (6th March 2018) - Simpson, Sue; Cook, Alison; Miles, Kathryn
Abstract : Objectives: The aim of this study is to report on the experiences, benefits, and challenges of patient and public involvement and engagement (PPIE) from a publicly funded early awareness and alert (EAA) system in the United Kingdom. Methods: Using email, telephone, a Web site portal, Twitter and focus groups, patients and the public were involved and engaged in the recognized stages of an EAA system: identification, filtration, prioritization, early assessment, and dissemination. Results: Approaches for PPIE were successfully integrated into all aspects of the National Institute for Health Research Horizon Scanning Research and Intelligence Centre's EAA system. Input into identification activities was not as beneficial as involvement in prioritization and early assessment. Patients gave useful insight into the Centre's Web site and engaging patients using Twitter has enabled the Centre to disseminate outputs to a wider audience. Conclusions: EAA systems should consider involving and engaging with patients and the public in identification, prioritization, and assessment of emerging health technologies where practicable. Further research is required to examine the value and impact of PPIE in EAA activities and in the early development of health technologies.